Peran Shooping Life Style Sebagai Variabel Mediasi Antara Hedonic Shooping Value Dan Utilitarian Value Terhadap Impulse Buying Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Muhammadiyah Metro - Selamet Fuadi; Yateno; Bergita Novilan (Jurnal Manajemen DIVERSIFIKASI, 2024)
Shopping is generally just buying the materials or products that are needed, but with the many variations of various products today, students of the Faculty of Economics and Business at Muhammadiyah Metro University spend more time choosing materials or products that are not only needed but also wanted and cause purchases suddenly without regard to the benefits of these goods. The factors that encourage students to do impulse buying include promotions/discounts, attractive models or just satisfying feelings. This research was conducted at Muhammadiyah Metro University. This study aims to determine the role of shopping lifestyle as a mediating variable between hedonic shopping values ​​and utilitarian values ​​on impulse buying in students of the Faculty of Economics and Business, University of Muhammadiyah Metro. This study used 92 respondents as the research sample and the sampling technique used accidental sampling. The data analysis method used is a quantitative analysis method including equation test, model test and hypothesis test. The results of this study indicate that the two independent variables, namely hedonic shopping value and utilitarian value, have an effect on impulse buying and the shopping lifestyle variable mediates these two variables so that each variable has an effect on impulse buying.